STRATEGI PENGEMBANGAN KOPERASI BERDASARKAN PREFERENSI DAN PENGARUHNYA TERHADAP VOLUME USAHA - Mahirun Mahirun (LPPM Universitas Pekalongan, 2015)
The purpose of this study was to determine the preferences of savings and loan cooperatives in an effort to increase business volume, and to find out the relationship between the policies of Pekalongan City Government and the volume of savings and loan cooperatives. The objects in this study were Kospin Jasa Pekalongan, KSP Lohjinawe, and KSP Panca Budi Mulya. The method used is the preference matrix and multiple linear regression analysis. The results show that marketing/promotion is the main factor desired by cooperatives with a scale of 2.0457. The distribution channel is the second factor desired by the savings and loan cooperatives in utilizing the policies provided by the Pekalongan City Government, with a scale of 1.7523. Management is the third factor that must be considered with the scale obtained by 1.4690. Capital is the fourth factor with a scale of 1.1790. The market share is the fifth factor that must be met with the scale obtained at 1.1690. On the results of correlation analysis it is known that the magnitude of the relationship between X1 (capital/funding), X2 (Management), X3 (Marketing/ promotion), X4 (Distribution channel), X5 (market share) with Y (Business volume) is 0, this means that the relationship between the policies of Pekalongan City Government in the field of capital/funding, management, marketing/promotion, distribution channels and the provision of market share with the business volume of savings and loan cooperatives in a very low category.